River Mumma - Reid-Benta, Zalika (Erewhon, an imprint of Kensington Publishing Corp., 2023)
"Alicia has been out of grad school for months. She has no career prospects and lives with her mom, who won't stop texting her macabre news stories and reminders to pick up items from the grocery store. Then, one evening, the Jamaican water deity, River Mumma, appears to Alicia, telling her that she has twenty-four hours to scour the city for her missing comb. Alicia doesn't understand why River Mumma would choose her. She can't remember all the legends her relatives told her, unlike her retail co-worker Heaven, who can reel off Jamaican folklore by heart. She doesn't know if her childhood visions have returned, or why she feels a strange connection to her other co-worker Mars. But when the trio are chased down by malevolent spirits called duppies, they realize their tenuous bonds to each other may be their only lifelines. With the clock ticking, Alicia's quest through the city broadens into a journey through time--to find herself and what the river carries." --